2023
DOI: 10.1186/s13073-023-01198-z
|View full text |Cite
|
Sign up to set email alerts
|

Systematic genomic analysis of SARS-CoV-2 co-infections throughout the pandemic and segregation of the strains involved

Abstract: Background SARS-CoV-2 recombinants involving the divergent Delta and Omicron lineages have been described, and one of them, “Kraken” (XBB.1.5), has recently been a matter of concern. Recombination requires the coexistence of two SARS-CoV-2 strains in the same individual. Only a limited number of studies have focused on the identification of co-infections and are restricted to co-infections involving the Delta/Omicron lineages. Methods We performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 30 publications
0
7
1
Order By: Relevance
“…The co-infection frequency was higher than reported elsewhere [8, 9], although the frequencies of individual projects ranged widely (0.15–2.03) (). Moreover, higher co-infection rates were found in the Spanish and South African projects (1.04 and 2.03 %, respectively).…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…The co-infection frequency was higher than reported elsewhere [8, 9], although the frequencies of individual projects ranged widely (0.15–2.03) (). Moreover, higher co-infection rates were found in the Spanish and South African projects (1.04 and 2.03 %, respectively).…”
Section: Resultscontrasting
confidence: 55%
“…In our previous study performed in Madrid [9], we identified a proportion of co-infection candidates that were likely due to co-existence of variants emerging in immunosuppressed patients or to laboratory contaminations. However, in this current study, Continued the unavailability of comprehensive epidemiological, laboratory and clinical data and the constraints of sample resequencing hinder the replication of some of the validation procedures applied in our prior work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our targeted long-read sequencing approach is also equipped for recovery of haplotype-resolved viral genomes. To our knowledge, our study is the first to provide a pandemic-wide, high-resolution evaluation of co-infections at this scale, though there have been other systematic efforts that are smaller 40 or target specific types of co-infections, e.g. Omicron/Delta 37 .…”
Section: Discussionmentioning
confidence: 99%
“…During the year 2023, a new phenomenon has occurred in the evolution of SARS-CoV-2 lineages with the emergence of recombinant variants, resulting from the existence of patients coinfected with more than one strain. Systems have been developed for the optimized identification of these coinfections from whole genome sequences, which allow determining that these recombinant variants have existed throughout the pandemic, contributing to the evolutionary acquisition of diversity in this virus, together with the accumulation of sequential mutations [ 19 ]. However, the evolutionary advantages of recombination arise especially when the co-infecting strains are markedly different; hence, attention began to be paid to the recombination phenomenon when the genomic diversity of circulating SARS-CoV-2 was highest, during the Omicron waves, when the BA.1, BA,2 , BA.5 lineages, among others, were prevalent [ 20 ].…”
Section: What Variants Have Circulated During This Year In the World ...mentioning
confidence: 99%